2022
DOI: 10.1021/acscatal.2c01078
|View full text |Cite
|
Sign up to set email alerts
|

A Monodisperse ε′-(CoxFe1–x)2.2C Bimetallic Carbide Catalyst for Direct Conversion of Syngas to Higher Alcohols

Abstract: Higher alcohol synthesis (HAS) from syngas through nonpetroleum carbon resources is quite prospective but still challenging owing to the unsatisfactory selectivity and catalytic stability. Here, we proposed a monodisperse ε′-(Co x Fe1–x )2.2C alloy carbide catalyst derived from Co x Fe3–x O4 spinel oxide nanoparticles, which was applied in the HAS reaction. The Co/Fe molar ratio showed a significant impact on the evolution of active sites, and the catalyst with a Co/Fe molar ratio of 1/2 contained the highest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 65 publications
1
12
0
Order By: Relevance
“…As shown in Figure b–e, both Fe 3 O 4 corroborated by two sextets (blue) and Fe 5 C 2 corroborated by three sextets (green) were found in all four spent catalysts. A small doublet in s-FeMg attributed to superparamagnetic Fe 3+ may belong to poorly crystallized iron oxide . Notably, another sextet (purple) with H = 18.45 ± 0.11 T, IS = 0.23 ± 0.04 mm·s –1 , and QS = 0.05 ± 0.01 mm·s –1 attributed to Fe 2.2 C was observed in s-FeM catalysts once the Fe–oxide interfaces were engineered, consistent with XRD results.…”
Section: Resultssupporting
confidence: 83%
“…As shown in Figure b–e, both Fe 3 O 4 corroborated by two sextets (blue) and Fe 5 C 2 corroborated by three sextets (green) were found in all four spent catalysts. A small doublet in s-FeMg attributed to superparamagnetic Fe 3+ may belong to poorly crystallized iron oxide . Notably, another sextet (purple) with H = 18.45 ± 0.11 T, IS = 0.23 ± 0.04 mm·s –1 , and QS = 0.05 ± 0.01 mm·s –1 attributed to Fe 2.2 C was observed in s-FeM catalysts once the Fe–oxide interfaces were engineered, consistent with XRD results.…”
Section: Resultssupporting
confidence: 83%
“…Some recent works also explore other types of bimetallic active sites such as Fe 2.2 C–Au, CoFe alloy bimetallic carbide, , binary Co/Mo carbide, bimetallic CoGa, , and Co 2 C–Mn 5 O 8 . To strengthen CO insertion, binary CO nondissociative metal sites such as Co 0 –Co 2 C/Ru δ+ (or Rh δ+ ) and Co 0 –Co 2 C/Cu 0 are also proposed. , Zeng et al fabricated an α-Al 2 O 3 -supported Janus-structured Fe 2.2 C–Au dual-site for HAS, which achieved a selectivity to total alcohols of 52.5% with 60.4% being C 2+ OH under 20% CO conversion.…”
Section: Higher Alcohol Synthesismentioning
confidence: 99%
“…146 kinetic coordination between chain growth and CO insertion, which largely benefits the production of C 5+ OH. Some recent works also explore other types of bimetallic active sites such as Fe 2.2 C−Au, 148 CoFe alloy bimetallic carbide, 145,169 binary Co/Mo carbide, 170 bimetallic CoGa, 171,172 and Co 2 C−Mn 5 O 8 . 142 To strengthen CO insertion, binary CO nondissociative metal sites such as Co 0 −Co 2 C/Ru δ+ (or Rh δ+ ) and Co 0 −Co 2 C/Cu 0 are also proposed.…”
Section: Higher Alcohol Synthesismentioning
confidence: 99%
“…Recently, Li et al reported that the highly dispersed Fe 5 C 2 nanoclusters (∼2 nm) were confined over the surface of Cu nanoparticles (∼25 nm) to form abundant Fe 5 C 2 –Cu interfacial sites, which exhibited a high CO conversion of 53.2% with a selectivity of 14.8 mol % for C 5+ alcohols. Zeng et al prepared a monodisperse ε′-(Co x Fe 1– x ) 2.2 C alloy carbide catalyst with a high HA selectivity of 35.8% at CO conversion of 20.8%. , However, the catalytic activity is still low, and the yield of higher oxygenates needs to be further improved.…”
Section: Introductionmentioning
confidence: 99%
“…In order to promote the production of higher oxygenates from syngas with high selectivity and activity, it is required to tailor the synergistic effect of dual active sites through careful design of the interface structure. Recently, Li et al reported that the highly dispersed Fe 35,36 However, the catalytic activity is still low, and the yield of higher oxygenates needs to be further improved. Layered double hydroxides (LDHs) have been widely employed as catalyst precursors due to the unique structure with adjustable metal cations.…”
Section: ■ Introductionmentioning
confidence: 99%